Representasi Artistik Kebudayaan Indonesia dalam Film Animasi "Raya and the Last Dragon" - Panjaitan, Angelia; Rachman, Anung (Rekam, 2023)
Raya and The Last Dragon is one of the first animated fantasy films produced by Disney that elevates and displays the cultural identities of Southeast Asia, including Indonesia, Vietnam, Thailand, Malaysia, Laos and Singapore. This animated film depicts a fantasy world called Kumadera country which is divided into five regions namely Heart, Fang, Spine, Talon and Tail. The five regions seem to describe the diverse Indonesian nation "Bhinneka Tunggal Ika" which means the unity and oneness of the Indonesian nation. This animated film is packed with artistic elements of Indonesian culture including Wayang kulit, batik, keris, pencak silat, gamelan, gadang houses, food, and people's behavior. This animated film applies the artistic design of several visual elements such as location sets, decorations, props, costumes and all work units that represent Indonesian culture. This research method uses descriptive qualitative using artistic theory and Roland Barthes semiotic cultural approach. The results of this study were analyzed using artistic theory and contextual understanding of signs and meanings from Roland Barthes' semiotic theory which divides the meaning systems of denotation, connotation and myths that implement Indonesian culture.